Financial Cryptography and Data Security - Tsudik, Gene (Springer, 2017)
This book constitutes the thoroughly refereed post-conference proceedings of the 12th International Conference on Financial Cryptography and Data Security, FC 2008, held in Cozumel, Mexico, in January 2008.